Uma edição de si: as meninas do YouTube - Sousa, Grasiele (2015)
This research proposes an analysis of amateur videos on beautification practices posted on the YouTube platform placed in the Internet. The authors of these videos are women of different ages and various social classes. They share their opinions on the strategies and beautification products in a very personal way in front of the camera. This all happens in a homemade movie set, usually in their sleeping room. Other places can also be the set, so that all things can be done in an informal atmosphere, more suitable to a direct and friendly conversation with the audience . YouTube is a platform for sharing videos that became popular in a short period. Since the mid 2000s it won thousands of users across the globe. Something comparable to the range of previous forms of communication for the purpose of audiovisual broadcasting and television, except for the fact that now we are talking about a type of interaction in which we are all potentially transmitters and receivers of information. In this work, we will give attention to some aspects of the way these videos are being produced and what seemed, to some extent: be related to an inherited experience of communication on television; happen as a way to update beautification practices of the past (like the so called beauty meetings ); be a way to produce subjectivities through a "self-editing process." The research grows from a sampling of the videos (more qualitative than quantitative) the construction of a logbook and a survey on the literature of the history of YouTube, the language of video, television and today's consumer society